PENERAPAN ONE DAY ONE PAGE TERHADAP PENINGKATAN MENGHAFAL AL-QUR’AN - Ferry Yanto; Moh. Zahiq; Imam Syafii (STAI Darussalam Lampung, 2023)
The purpose of this study was to discuss the application of the One Day One Page method. the research method uses qualitative research methods with a descriptive attitude. Data collection using documentation, observation and interviews. The results stated that the implementation of the One Day One Page method was able to improve memorisation. In its application, first, students are told to pray, second, recite one page of muroja'ah, third, after students do muroja'ah who are sure of their memorisation, then deposit their memorisation from beginning to end. Even though what is memorised is only one page, what students deposit is not only the page they memorised but also the previous page that has been deposited is also deposited again.